The Impact of Studying Abroad on Economic Activity of Graduates - Jacek Liwinski (Institute of Economic Research (IER), 2017)
Research background: Over 200,000 of European students study abroad under the Erasmus mobility program in the course of their higher education. It seems that employers may treat students' participation in international exchange programs as a signalling tool, since according to them international students' skills - both cognitive and non-cognitive - are well above the average. On the other hand, students participating in exchange programs underline a positive impact of studying abroad on their personal development, i.e. on their general skills. Thus, from a theoretical point of view we may expect a positive correlation between studying abroad and economic activity after graduation, which follows from both signalling theory and human capital theory. On the average, 54% of European students report that participation in Erasmus exchange program helped them to obtain the first job, but interestingly, those from the CEE countries, including Polish students, report it much more often. Purpose of the article: The aim of this paper is to determine whether studying abroad has an impact on the employment rate of higher education graduates in Poland over the first few years after graduation. Methodology/methods: We used the propensity score matching (PSM) method and data from a representative, nationwide tracer survey of Poles who graduated from secondary schools or higher education institutions over the period of 1998-2005. Findings: The results of the analysis show that Polish students who completed at least one semester of their studies abroad do not benefit in terms of a higher employment rate after graduation.
Keywords: I23; I26; J21; J24; 330; studying abroad; human capital; graduates; employment rate; PSM method